Fragilité et résilience des liens entre le milieu insulaire et ses populations. Le cas de Peng Chau à Hong-Kong - Myriem Alnet; Camille Salgues (Espace populations sociétés)
Based on the case of Peng Chau, a small 1 km² island with 5,700 inhabitants in the Hong Kong archipelago, this article examines how the island’s inhabitants and environment are engaged in a contingent relationship, characterized by fragile yet resilient bonds. To explore this, an original field study (participant observation, interviews, and mapping) was carried out on three characteristic "goods" of the island: local T-shirts, outdoor chairs, and papayas. The analysis, supported by a theoretical framework on different types of goods in economics, highlights both the importance of the population’s characteristics (in terms of ethnic lines, sectors of activity, and age profiles) and the particular relevance of the local scale (that of the island)—while acknowledging that larger or individual scales may also play a role—in understanding certain ways of fostering commonality. This contemporary fieldwork is consistently contextualized within the island’s longer history. The article, co-authored, reflects the exchanges between the academic world and local community actors in the field. It draws freely from several disciplines: geography, anthropology, demography, urban planning, and economics.